2019
DOI: 10.1002/alr.22369
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of endoscopic sinus surgery in the management of adult chronic rhinosinusitis

Abstract: Background: There is a striking lack of long-term, prospective outcomes data for endoscopic sinus surgery (ESS) in chronic rhinosinusitis (CRS) using validated instruments. Our primary objective in this study was to report longterm outcomes (>10 years) a er ESS for CRS obtained by prospective data collection.Methods: An observational cohort (n = 59) of adult patients with CRS electing ESS was enrolled between 2004 and 2008. Long-term, disease-specific quality-oflife (QOL) outcomes, health utility values (HUV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 44 publications
2
58
0
1
Order By: Relevance
“…21 Prior studies in the otolaryngology literature have also used validated tools to examine aspects of patient satisfaction beyond its relationship with telemedicine. For example, the impact of long-term outcomes, 22 surgical interventions, 23 patient education, 24,25 and multidisciplinary clinics on patient satisfaction has been evaluated. 26 Uniquely, the present study focused on patient satisfaction, and the quality of the physician-patient interaction, ensuring that it was not compromised in the virtual setting compared to traditional in-person clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…21 Prior studies in the otolaryngology literature have also used validated tools to examine aspects of patient satisfaction beyond its relationship with telemedicine. For example, the impact of long-term outcomes, 22 surgical interventions, 23 patient education, 24,25 and multidisciplinary clinics on patient satisfaction has been evaluated. 26 Uniquely, the present study focused on patient satisfaction, and the quality of the physician-patient interaction, ensuring that it was not compromised in the virtual setting compared to traditional in-person clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants included adult human subjects previously recruited for an observational, investigator‐monitored research study funded by the National Institute on Deafness and Other Communication Disorders (NIH Grant 2R01 DC005805), conducted between March 2011 and June 2015. Additional findings from this study cohort have been published elsewhere 11‐16 . Participants were prospectively enrolled via invitation from a patient population referred to 4 academic rhinology practices located in North America, including Oregon Health and Science University (OHSU, Portland, OR), Stanford University (Palo Alto, CA), the Medical University of South Carolina (Charleston, SC), and the University of Calgary (Calgary, AB, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…A larger study that included nearly 30,000 patients who had undergone FESS for CRS reported 75% of CRSwNP patients required only 1 surgery in a mean follow‐up of 10 years 14 . Oral steroids and antibiotics are typically reserved for severe polyposis and acute exacerbations, and prospectively followed patients have shown improvement in long‐term quality‐of‐life measures 15,16 . However, despite these efforts, there is a subset of patients who fail this algorithm, requiring revision surgery or possibly multiple revision surgeries 17 …”
Section: Recalcitrant Nasal Polypsmentioning
confidence: 99%